Africa and the New Silk Roads - (:unkn) unknown (My University, 2018)
This contribution raises the question of the place the New Silk Roads strategy could reserve for Africa and its 54 economies. To answer this question, we will begin by highlighting the very limited economic importance of Africa for China (first investment, second trade), and then I will examine the strategic role that Africa as a whole and African states are likely to play for China. This research will be conducted on the basis of existing documents, whether official reports (administrative or management), scientific studies or more journalistic information. Wherever possible, it will favour first-hand Chinese documents.
Keywords: African Research